2020
DOI: 10.1177/0886368719900032
|View full text |Cite
|
Sign up to set email alerts
|

The Inevitable Rise in Dual-Income Households and the Intertemporal Effects on Labor Markets

Abstract: The number of dual-income households has been steadily increasing over the past few decades. This study supports the hypothesis that given a household’s desire to remain above a minimum threshold standard of living, the rise in the number of dual-earner households is inevitable mostly due to inflationary pressures in product markets including rising housing prices and child care costs coupled with relatively flat wage trends. Mitigating uncertainty and risk associated with shifts in retirement plan offerings—m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Intergenerational coparenting has become more prevalent over the past 2 decades as a result of an increasing aging population, such that many more grandparents are available to help with parenting (Chiang & Park, 2015). Additionally, scholars have suggested that the influx of single-parent homes and the growing number of dual-income families have resulted in the need for additional childrearing support (Leonce, 2020). However, the reliance on multiple generations to raise children may have its roots in evolutionary adaptiveness.…”
Section: Research Evidence On Intergenerational Familiesmentioning
confidence: 99%
“…Intergenerational coparenting has become more prevalent over the past 2 decades as a result of an increasing aging population, such that many more grandparents are available to help with parenting (Chiang & Park, 2015). Additionally, scholars have suggested that the influx of single-parent homes and the growing number of dual-income families have resulted in the need for additional childrearing support (Leonce, 2020). However, the reliance on multiple generations to raise children may have its roots in evolutionary adaptiveness.…”
Section: Research Evidence On Intergenerational Familiesmentioning
confidence: 99%
“…This has coincided with changing perspectives regarding the role of each partner in the household, and a desire to maintain a minimum threshold standard of living (Blossfeld and Kiernan, 1995;Donnelly et al, 2016). Due to an increase in living and housing costs, maintaining such a minimum living standard made the rise in dual-earner households almost inevitable (Leonce, 2020). The introduction of women into the workforce was one of the drivers behind the second trend: rise of the service sector (Rendall, 2018).…”
Section: Introductionmentioning
confidence: 99%